Inferior Vena Cava Filter and Catheter-based Thrombolysis for Treatment of Massive Deep Vein Thrombosis: A Case Report - Sangram S Mangudkar; Sanket Genuji Shinde; Varun Bhaskar Lingneni; Satbir Kaur Malik; Sai Sirisha Nallani (Journal of Clinical and Diagnostic Research)
Deep Vein Thrombosis (DVT), a subtype of Venous Thromboembolism (VT) is more likely to occur in areas such as the lower leg, thigh or pelvis when vessel wall damage, blood flow stasis and hypercoagulability are present. Untreated DVT in the lower extremities can enlarge and result in further complications such as Post Thrombotic Syndrome (PTS) and an elevated risk of pulmonary thromboembolism. Prothrombotic anomalies may arise as a result of a variety of circumstances including the degree and type of infection, inflammation, bed rest, the use of mechanical ventilators and venous catheterisation. The rise in DVT cases in recent years along with thrombus complications in various patient populations calls for customised DVT care and intervention. This research was carried out on a young man without any notable medical history and no history of addictions who arrived complaining of severe swelling that had developed over the course of a day, affecting his left lower limb. A bilateral lower limb doppler ultrasound suggested thrombosis in the popliteal vein, great saphenous vein, deep femoral vein and common femoral vein in the left lower limb. Low molecular weight heparin injection was used to treat the patient. However, as the patient had not shown any significant signs of clinical improvement, an Inferior Vena Cava (IVC) filter was inserted to prevent pulmonary thromboembolism, and catheter-based thrombolysis was performed to break down clots and restore blood flow, thereby reducing the risk of long-term complications like PTS. Following recovery, the patient was discharged on oral anticoagulants and is currently on regular follow-up.